2008
DOI: 10.1128/mcb.01647-07
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Communication between the Silencers of HMR

Abstract: Gene regulation involves long-range communication between silencers, enhancers, and promoters. In Saccharomyces cerevisiae, silencers flank transcriptionally repressed genes to mediate regional silencing. Silencers recruit the Sir proteins, which then spread along chromatin to encompass the entire silenced domain. In this report we have employed a boundary trap assay, an enhancer activity assay, chromatin immunoprecipitations, and chromosome conformation capture analyses to demonstrate that the two HMR silence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 64 publications
5
61
1
Order By: Relevance
“…Later studies suggested that the HM loci also fold back upon themselves, consistent with earlier findings that the DNA supercoiling of the silenced domains was altered (Bi and Broach 1997;Cheng et al 1998;Valenzuela et al 2008). Molecular genetic studies showed that distant silencers synergize one another, as if they interact physically Fourel et al 1999;Pryde and Louis 1999;Cheng and Gartenberg 2000;Oki et al 2004;Valenzuela et al 2008). Even silent chromatin domains separated by great distances, like the HM loci at the ends of chromosome III, have been shown to interact ( Figure 2C); in essence by folding back upon one another (Lebrun et al 2003;Miele et al 2009;Kirkland and Kamakaka 2013).…”
Section: Higher-order Structures Within Silenced Chromosomal Domainssupporting
confidence: 76%
See 1 more Smart Citation
“…Later studies suggested that the HM loci also fold back upon themselves, consistent with earlier findings that the DNA supercoiling of the silenced domains was altered (Bi and Broach 1997;Cheng et al 1998;Valenzuela et al 2008). Molecular genetic studies showed that distant silencers synergize one another, as if they interact physically Fourel et al 1999;Pryde and Louis 1999;Cheng and Gartenberg 2000;Oki et al 2004;Valenzuela et al 2008). Even silent chromatin domains separated by great distances, like the HM loci at the ends of chromosome III, have been shown to interact ( Figure 2C); in essence by folding back upon one another (Lebrun et al 2003;Miele et al 2009;Kirkland and Kamakaka 2013).…”
Section: Higher-order Structures Within Silenced Chromosomal Domainssupporting
confidence: 76%
“…However, the notion of a silent chromatin-mediated fold back was supported by the use of novel, transcriptional-reporter constructs that detected long-range interactions within silenced subtelomeric regions (de Bruin et al 2001). Later studies suggested that the HM loci also fold back upon themselves, consistent with earlier findings that the DNA supercoiling of the silenced domains was altered (Bi and Broach 1997;Cheng et al 1998;Valenzuela et al 2008). Molecular genetic studies showed that distant silencers synergize one another, as if they interact physically Fourel et al 1999;Pryde and Louis 1999;Cheng and Gartenberg 2000;Oki et al 2004;Valenzuela et al 2008).…”
Section: Higher-order Structures Within Silenced Chromosomal Domainsmentioning
confidence: 64%
“…4C), because it causes ADE2 derepression while maintaining URA3 repression. This effect of tethered Rpd3 is the same as that of Sas2 at the two loci (32) and shows that Rpd3 is not only a "desilencer" but can be classified as a "true barrier" factor. These results show that targeting of the HDAC Rpd3 disrupts heterochromatin spreading.…”
Section: Resultsmentioning
confidence: 60%
“…The process repeats until Sir2-4 protein complexes bind and modify the nucleosomes that compose the silent loci (reviewed in Rusche et al 2003;Moazed et al 2004). The binding of the Sir2-4 protein complexes may directly repress transcription and/or lead to higher-order looping and compaction that renders the underlying DNA less accessible (Vazquez and Schedl 1994;Cheung et al 2000;Sekinger and Gross 2001;Valenzuela et al 2008).…”
mentioning
confidence: 99%